2016
DOI: 10.1007/s00702-016-1517-6
|View full text |Cite
|
Sign up to set email alerts
|

MMSE and MoCA in Parkinson’s disease and dementia with Lewy bodies: a multicenter 1-year follow-up study

Abstract: The Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA) are the most commonly used scales to test cognitive impairment in Lewy body disease (LBD), but there is no consensus on which is best suited to assess cognition in clinical practice and most sensitive to cognitive decline. Retrospective cohort study of 265 LBD patients [Parkinson’s disease (PD) without dementia (PDnD, N = 197), PD with dementia (PDD, N = 40), and dementia with Lewy bodies (DLB, N = 28)] from an international … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 43 publications
5
78
1
2
Order By: Relevance
“…However, future work might explore this further in a larger PD sample. We also acknowledge that the MMSE is considered a less sensitive measure of cognitive status in PD compared to the Montreal Cognitive Assessment Battery (MOCA; Nasreddine et al, 2005), as the MOCA also assesses executive, visuospatial and memory abilities (Aarsland, 2016;Biundo et al, 2016). A limitation of our study may be the inclusion of some PD individuals in the earliest stages of dementia, who were not detected using the MMSE.…”
Section: Discussionmentioning
confidence: 84%
“…However, future work might explore this further in a larger PD sample. We also acknowledge that the MMSE is considered a less sensitive measure of cognitive status in PD compared to the Montreal Cognitive Assessment Battery (MOCA; Nasreddine et al, 2005), as the MOCA also assesses executive, visuospatial and memory abilities (Aarsland, 2016;Biundo et al, 2016). A limitation of our study may be the inclusion of some PD individuals in the earliest stages of dementia, who were not detected using the MMSE.…”
Section: Discussionmentioning
confidence: 84%
“…16,17 . However, the sensitivity to change in DLB has been reported to be similar in MoCA and MMSE 18 . However, subdomain-specific cognitive decline has rarely been assessed in DLB.…”
Section: Cognitive Declinementioning
confidence: 97%
“…On the contrary, the Montreal Cognitive Assessment (MoCA) is a brief cognitive screening tool (Nasreddine et al 2005), which has shown high sensitivity and specificity for the assessment of cognitive deficits in PD (Gill et al 2008;Hoops et al 2009;Zadikoff et al 2008). Several studies already reported the superiority of MoCA over MMSE in general population (Luis et al 2009), in dementia with Lewy bodies (DLB), Alzheimer's disease (AD), and Huntington's disease (HD) (Biundo et al 2016;Hoops et al 2009;Nasreddine et al 2005;Videnovic et al 2010). However, experience in PSP and MSA is limited.…”
Section: Introductionmentioning
confidence: 96%